Uso da cama de frango associada à adubação mineral no sistema de produção de grãos da região oeste do Paraná - Fávero, Fernando (2012)
The production system of grains and meats in Brazil conducted the country to a ranking of the largest producers and exporters of food in the world. The integrated production of poultry generates defined quantities of waste. The chicken manure is rich in nutrients and can be so used as fertilizer in the crops. The knowledge of the responses related to the crops allows the utilization of the chicken manure in an adequate and a rational form, avoiding losses and reducing environmental impact. The objective was to evaluate the responses in the production of grains (soybeans, corn and wheat) with application of amounts of chicken manure before the winter crop, associated with mineral fertilizer (NPK). For this, an experiment was conducted in the Experimental Station of the Copacol in Cafelândia-PR with different doses of chicken manure (0, 2, 4, 6 and 8 t ha-1), and three systems of mineral fertilization (control, super phosphate simple and formulated) in the furrow of the seeding, during two years. The chicken manure was applied manually in the plots before the winter cultivation. The experimental design was defined as randomized complete block with plots subdivided in four replications. The total concentration of foliar N, P and K, yield components, biometric variables of the crop, grains' production of the cultivation and economic returns have been evaluated. After four cultivations, samples of the soil were obtained for determining its chemical properties. The chicken manure provided the increment of the contents of foliar N, P and K of the corn and soybean as well as modified the biometric variables, also increasing the yield of the grains of the studied crops. High doses of chicken manure applied before the wheat cultivation promote the lodging of the cultivation and reduction of the weight of the hectoliter, but enhancing the grains' yield. The greatest productivity of grains and the highest annual returns in the production system of the west of the Paraná were obtained with the doses of 7,39 t ha-1 yield-1 and 5,45 t ha-1 yield-1 of chicken manure, respectively. The fertilization with chicken manure increases the levels of P, K und S in the soil, where the saturation of K reduces the concentration of Cu in the soil. The chicken manure allows the partial substitution of mineral fertilizer, also promoting the highest investment return